2019
DOI: 10.1136/bmjopen-2018-026322
|View full text |Cite
|
Sign up to set email alerts
|

AIDS-related stigmatisation in the healthcare setting: a study of primary healthcare centres that provide services for prevention of mother-to-child transmission of HIV in Lagos, Nigeria

Abstract: ObjectiveTo assess AIDS stigmatising attitudes and behaviours by prevention of mother-to-child transmission (PMTCT) service providers in primary healthcare centres in Lagos, Nigeria.DesignCross-sectional survey.SettingThirty-eight primary healthcare centres in Lagos, Nigeria.ParticipantsOne hundred and sixty-one PMTCT service providers.Outcome measuresPMTCT service providers’ discriminatory behaviours, opinions and stigmatising attitudes towards persons living with HIV/AIDS (PLWHAs), and nature of the work env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 34 publications
0
13
1
Order By: Relevance
“…A recent study suggests that training of health providers can reduce fear of infection and therefore make them less likely to engage in discriminatory healthcare practices such as double gloving. 17 As suggested by participants, community education, and the involvement of male partners especially in couples counselling may be effective. It is important to recognise that influences on AIDS-related stigmatisation and discrimination are rooted in the structure of communities and societies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study suggests that training of health providers can reduce fear of infection and therefore make them less likely to engage in discriminatory healthcare practices such as double gloving. 17 As suggested by participants, community education, and the involvement of male partners especially in couples counselling may be effective. It is important to recognise that influences on AIDS-related stigmatisation and discrimination are rooted in the structure of communities and societies.…”
Section: Discussionmentioning
confidence: 99%
“…This study was embedded within a larger quantitative study, which methodology had previously been published. 17 Using a geopolitical map, we purposively selected central and western districts of the state for the study. These districts were chosen because they covered the largest areas of Lagos, including areas with populations with income levels that are most representative of the state.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not in the context of the ICDM model, health worker-related stigma of this nature has been reported in the provision of reproductive health care in Ilorin, Nigeria, largely due to misperceptions [ 43 ]. On the other hand, a study in Lagos, Nigeria showed that health workers were supportive of women living with HIV who wished to have babies [ 44 ]. In Ghana, a study showed that a higher sexual and reproductive health stigma score was linked with a history of pregnancy among adolescents [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…As far as HIV/AIDS is concerned, its transmission is largely associated with large population sizes and fluid movement of people in and out of the state. 19 A descriptive cross-sectional study was conducted among febrile patients who presented themselves for medical examination at Reddington Hospital, one of the many hospitals in Ikeja receiving malaria patients. To calculate our sample size, we used the prevalence of malaria and HIV coinfection (2.9%) previously reported in Ikeja, 20 and a precision (d) of 2%.…”
Section: Methodsmentioning
confidence: 99%